Potential market size and impact of hepatitis C treatment in low‐ and middle‐income countries. Issue 7 (29th February 2016) - Woode, M. E.; Abu‐Zaineh, M.; Perriëns, J.; Renaud, F.; Wiktor, S.; Moatti, J.‐P.
Summary: The introduction of direct‐acting antiviral agents (DAAs) has made hepatitis C infection curable in the vast majority of cases and the elimination of the infection possible. Although initially too costly for large‐scale use, recent reductions in DAA prices in some low‐ and middle‐income countries (LaMICs) has improved the prospect of many people having access to these drugs/medications in the future. This article assesses the pricing and financing conditions under which the uptake of DAAs can increase to the point where the elimination of the disease in LaMICs is feasible. A Markov simulation model is used to study the dynamics of the infection with the introduction of treatment over a 10‐year period. The impact on HCV‐related mortality and HCV incidence is assessed under different financing scenarios assuming that the cost of the drugs is completely paid for out‐of‐pocket or reduced through either subsidy or drug price decreases. It is also assessed under different diagnostic and service delivery capacity scenarios separately for low‐income (LIC), lower‐middle‐income (LMIC) and upper‐middle‐income countries (UMIC). Monte Carlo simulations are used for sensitivity analyses. At a price of US$ 1680 per 12‐week treatment duration (based on negotiated Egyptian prices for an all oral two‐DAA regimen), most of the people infected in LICs and LMICs would have limited access to treatment without subsidy or significant drug price decreases. However, people in UMICs would be able to access it even in the absence of a subsidy. For HCV treatment to have a significant impact on mortality and incidence, a significant scaling‐up of diagnostic and service delivery capacity for HCV infection is needed.